Potential Role of Sox9 in Patterning Tracheal Cartilage Ring Formation in an Embryonic Mouse Model - Elluru, Ravindhra G; Whitsett, Jeffrey A (Archives of otolaryngology--head & neck surgery, 2004)
OBJECTIVE To identify genes expressed early in the formation of the mouse trachea that control patterning of tracheal cartilaginous rings. DESIGN The mouse larynx and trachea begin as an outpouching from the ventral foregut endoderm at embryonic day (E) 9. Digoxigenin-labeled RNA probes to putative tracheal patterning genes were generated by in vitro transcription. Embryos ranging in age from E9 to E16 were then subjected to whole-mount in situ hybridization using these labeled RNA probes. The RNA probes were then localized using antidigoxigenin antibodies tagged with a reporter molecule. In this manner, the 3-dimensional spatial and temporal expression of putative tracheal patterning genes was examined. SUBJECTS F/VBN mice. RESULTS In the developing mouse trachea, the expression of Sox9 messenger RNA preceded cartilage ring formation. Sox9 was expressed as 2 distinct longitudinal stripes along the posterolateral aspect of the trachea as early as E9, when the developing trachea is first identified. Collagen 2A1, a cartilage-specific protein, was subsequently expressed in the same longitudinal pattern as Sox9, consistent with the early commitment of Sox9-expressing cells to the cartilage program. As cartilage rings formed, Sox9 and collagen 2A1 was expressed over the lateral and anterior aspects of the trachea. CONCLUSIONS We have developed a system to study the early expression of genes that may pattern the formation of the trachea. We have identified a gene (Sox9) with a known role in chondrocyte differentiation that is expressed in a highly specific temporal and spatial pattern in the developing upper respiratory tract.Arch Otolaryngol Head Neck Surg. 2004;130:732-736-->